Fiscal federalism, decentralization and economic growth: A meta-analysis - Tushyanthan Baskaran; Lars P. Feld; Jan Schnellenbach (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2016)
The theoretical literature on fiscal federalism has identified several channels through which government decentralization could affect economic growth. Much of the literature focuses on the efficiency aspects of a decentralized provision of public services, but decentralization may also increase growth by raising the ability of the political system to innovate and carry out reforms. In contrast, some authors argue that decentralization increases corruption and government inefficiency, and thus may diminish growth. Given this theoretical ambiguity, several studies have attempted to identify the effect of decentralization on economic growth empirically over the last two decades. We review and conduct a meta-analysis of this empirical literature. Based on our analysis, we point out open questions and discuss possible ways to answer them.
Keywords: 330